Distribution and features of middle cerebral artery atherosclerotic plaques in symptomatic patients: a 3.0 T high-resolution MRI study. (20th May 2015) - Sui, Binbin; Gao, Peiyi; Lin, Yan; Jing, Lina; Qin, Haiqiang
Abstract : Objectives: To investigate the distribution and features of middle cerebral artery (MCA) atherosclerotic plaques in patients with acute ischaemic strokes using high-resolution magnetic resonance (MR) imaging. Methods: Forty-six plaques from 44 MCAs (18 right and 26 left) in patients with acute symptomatic ischaemic strokes were studied. High-resolution MR imaging including tb1 weighted imaging (T1WI), tb2 weighted imaging (T2WI), PD weighted imaging (PDWI) and three-dimensional magnetization-prepared rapid acquisition gradient-echo (MPRAGE) sequences were used to visualise the plaques. The locations of plaques were classified into ventral, distal, superior and inferior wall of the MCA on oblique sagittal images. The thickness, area and signal intensities of plaques were recorded. The stenosis degree of MCA was calculated. Results: Among all 46 plaques, 26 plaques were located at the ventral wall (56.5%), 6 at the dorsal wall (13.0%), 9 at the superior wall (19.6%), and five at the inferior wall (10.9%). The average thickness and area of plaques were 1.37 ± 0.53 mm (range: 0.61–3.20 mm) and 3.80 ± 2.13 mm 2 (range: 1.01–12.2 mm 2 ), respectively. No significant differences in plaque thickness ( P  = 0.464), plaque area ( P  = 0.107) or stenosis degree ( P  = 0.563) were noted between different locations. Most of the plaques (44/46) showed iso-intensity on tbl1WI. On tbl2WI and PDWI, 24 plaques showed iso-intensity, 12 plaques showed a slightly high signal intensity (SI), and eight plaques showed a slightly low SI. Intraplaque haemorrhage was found in two plaques, with high SI on tbl1WI and MP-RAGE and high or mixed SI on tbl2WI and PDWI. Discussion: Middle cerebral artery plaques in patients with acute infarction have certain tendency to locate at ventral and superior walls. Distribution and features of plaques revealed some plaque formation characteristics and would help to understand underlying mechanisms of ischaemic events.